The potential of glomalin-related soil proteins as a sensitive indicator of changes in different cropping systems in the Argentine Pampas - Commatteo, Jaqueline Giselle; Barbieri, Pablo; Corral, Raúl Alejandro; Covacevich, Fernanda (Springer, 2024)
The glomalin-related soil proteins (GRSPs) are currently used to describe different fractions of the protein, which are linked to the arbuscular mycorrhizal fungal activity and include the easily or total GRSP (named EE or T, respectively) extracted. The GRSP would represent part of the carbon storage, but there are still disagreements whether the GRSP is a reliable indicator of changes in agricultural practices. We aimed (i) to determine the sensitivity of GRSP as an indicator of soil changes in different cropping systems, (ii) to evaluate the accuracy of relationships between GRSP and soil organic carbon (SOC) and (iii) to improve the T-GRSP standard procedure. Three long-term field trials were studied in the Argentine Pampas during winter and autumn over two growing seasons of soybean under three cropping regimes: soybean monoculture (Sb) and agricultural intensification that included cover crop (CC) before soybean (CC/Sb) or CC/soybean-corn-double cropping with wheat and soybean, called crop rotation (CR). Significant SOC increases were found only in the intensified plots with a low initial SOC. The optimization of T-GRSP procedure that included the sum of GRSP content across all generated extracts, and having stopped the extraction procedure when the value of absorbance reached 0.04?0.09, rather than processing samples based on their color, allowed us to achieved more accurate results; also, lower volume of the centrifuge tubes used reduced the processing time. The GRSP positively correlated to SOC and, in general, highest EE-GRSP and T-GRSP concentrations were recorded (mainly in winter-fallow) under agricultural intensification. This should be considered before planning agricultural production decisions in order to maintain soil sustainability.